Characteristics and Physical Activity Depression Risk 1-3 Months Postpartum - Rizky Amelia; Listyaning Eko Martanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Postpartum depression is a mood disorder that occurs after childbirth and reflects the psychological dysregulation that is a sign of major depression symptoms. The incidence rate in Indonesia is between 50-70% of postpartum women. It is known that age, education level, employment status, income, family type, BMI, parity, type of delivery, number of living children, exclusive breastfeeding and physical activity affect postpartum depression. Knowing the effect of age, education level, employment status, income, family type, BMI, parity, type of delivery, number of living children, exclusive breastfeeding and physical activity on postpartum depression. This study used a quantitative analytic method, with a cross-sectional technique. It was conducted from August to October 2020. The sample of this study was 62 respondents who had babies aged 1 - 3 months. The research instrument used the IPAQ to measure physical activity data and the EPDS to measure the risk of postpartum depression. There was a relationship between age (p = 0.008) and BMI (p = 0.030) with the risk of developing postpartum depression (bivariate analysis) and there was a simultaneous relationship between family type factors (p = 0.002), exclusive breastfeeding (p = 0.001) and activity. physical (p = 0.008) with a risk of postpartum depression. Factors of age, BMI, family type, exclusive breastfeeding and physical activity influence the occurrence of postpartum depression. Attention in the form of help from others to care for themselves or their babies and their daily needs, comfort to reduce fatigue as a triggering factor for postpartum depression